Empirical investigation of supply disruption in plastic SMEs. (18th August 2021) - Raghuram, P.; Jawahar, Dhianeshwar
Supply disruption is the major reason for closure of small and medium scale (SMEs) plastic industries. Plastic recycling process and raw material quality are the major factors affecting the competence of the manufacturer. In this paper, we develop an empirical framework to ascertain relationships between the various influencing factors of supply disruption leading to closure of SMEs. A theoretical model is proposed taking into account all the identified factors leading to supply disruption. To validate this theoretical model, structural equation modelling (SEM) is used by collecting data from 195 plastic SMEs. From the results obtained, it was found that financial status, irregular supply of scrap, unavailability of labour and quality of the raw material are the major issues affecting the supply chain. By taking evasive action, start-ups as well as existing companies can avoid the causes of supply disruption resulting in improved performance measures.